CURUG CIANGIN RIVER SIDE CAMP: AN ISLAMIC PERSPECTIVE OF MARKETING MIX ANALYSIS - Asep Kurniawan; Afghani Mahmuda Bahreisy; Ida Erlinda (STIESA Press, 2024)
This study aims to analyze the application of the marketing mix at Curug Ciangin River Side Camp as a camping destination. The research method uses a qualitative approach with descriptive techniques. Data were collected through interviews with managers and visitors as well as direct observations on site. The findings reveal that the marketing mix, which consists of product, price, promotion, place, people, process, and physical evidence, plays a significant role in attracting and retaining tourists' interest in visiting Curug Ciangin River Side Camp. The analysis shows that the product offered, such as camping packages with strategic locations by the riverside, is the main attraction for tourists. Additionally, competitive pricing, word-of-mouth promotion, and an enjoyable location also contribute to attracting visitors. Human resource management involving local residents from Desa Cibeusi is one important strategy in increasing local community participation and reducing unemployment. Efficient service processes, from booking and registration to facilities provided and after-sales service, ensure the satisfaction and needs of tourists are met. Furthermore, physical evidence such as a comfortable environment and natural beauty also play a determining role in tourists' decisions to choose Curug Ciangin River Side Camp as a camping destination. Based on the analysis, this study provides several recommendations for the development of Curug Ciangin River Side Camp. These recommendations include enhancing local resident training, diversifying facilities, strengthening digital promotion, managing the environment well, and regularly collecting feedback from visitors. By implementing these suggestions, it is hoped that Curug Ciangin River Side Camp can continue to grow as an attractive tourist destination and provide sustainable benefits for the local community.